OB CHILDREN PROTECTION IN THE ISLAMIC LAW PERSPECTIVES - Bariah, Oyoh (AL-MASHALIH (Journal of Islamic Law), 2018)
Children protection is a discussion of human rights. Maintaining and protecting offspring or children including human rights are known as part of human rights in Islam. The concept of human rights, commonly known as HAM, in Islamic Law is called ad-Dlaruriyat al-Khamsah (five basic principles in Islamic law) which becomes the main goal of the whole Islamic Shari'a. Through literature review and case study related to children protection, this article is described. Children protection in the perspective of Islamic Law is the implementation of hifdz al-nasl and hifdz an-nafs that Islam is very concerned about the protection and rights of children while rejecting all forms of violence and oppression as well as persecution of children. Children protection in Indonesia has been ruled by the rules of Law No.23 of 2002 concerning Children Protection, Law no. 23 of 2004 concerning the Elimination of Domestic Violence and the Convention on the Rights of the Children.